1989
DOI: 10.1080/00268978900101581
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution spectra and analysis of the hot bands of the v2vibration of CF3Cl (v2+ vn- vn,n= 3, 5, 6)

Abstract: A detailed analysis is reported of high resolution I.R. spectra of CF3C1 (Freon 13, chlorotrifluoromethane) in the 750-800cm -1 range obtained by Fourier transform and diode laser spectroscopy. A comparison is made between hot-band transitions starting from a non-degenerate vibrational level (V 2 "~ ' i~ 3 --lP3) and those from two-fold degenerate levels (v 2 + v 5 -v 5 and v2 + v6 -v6). For the latter the effect of vibrational excitation on the Coriolis constant A( has been observed. The rotational analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Because the data were much better and more extensive for the CF 3 35 Cl species, the values of DD J , DD JK , and DD K were assumed to be the same for the two isotopomers as well as for the hot band. The resulting constants are given in Table 8 and agree with the earlier work of Nencini et al [28] and Bürger et al [19]. The analysis of the hot band m 2 + m 3 -m 3 was combined with the analysis of the difference band m 1 -m 3 because they both have the same lower state and contribute to the determination of the constants for m 3 .…”
Section: Analysis Of the M 5 Bandmentioning
confidence: 62%
See 2 more Smart Citations
“…Because the data were much better and more extensive for the CF 3 35 Cl species, the values of DD J , DD JK , and DD K were assumed to be the same for the two isotopomers as well as for the hot band. The resulting constants are given in Table 8 and agree with the earlier work of Nencini et al [28] and Bürger et al [19]. The analysis of the hot band m 2 + m 3 -m 3 was combined with the analysis of the difference band m 1 -m 3 because they both have the same lower state and contribute to the determination of the constants for m 3 .…”
Section: Analysis Of the M 5 Bandmentioning
confidence: 62%
“…The measurements given by Baldacchini et al [26] and by Nencini et al [28] were useful for verifying the assignments we found for both isotopic species. The present work used a gas sample that contained the natural abundance of isotopes and so allowed us to determine an accurate value for the isotopic shift for m 2 .…”
Section: The M 2 Band Near 783 Cm à1mentioning
confidence: 69%
See 1 more Smart Citation